Polarizing plate, polarizing plate with retardation layer, and image display device
By using a polyvinyl alcohol (PVA) base film on the polarizer and adding an extremely thin protective layer, the problem of the extremely thin polarizer being prone to cracking when heated is solved, and excellent optical performance and thermal crack resistance are achieved. It is suitable for flexible and foldable display devices.
Patent Information
- Application Number
- JP2024218628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-08-06
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing extremely thin polarizers are prone to cracks when heated and are difficult to maintain excellent optical performance.
A polarizer made of polyvinyl alcohol (PVA) base film is used and a protective layer of 10 μm or thinner is plated on one side of the polarizer. The thermal crack resistance of the polarizer is improved by controlling the directionality of the PVA and the thickness of the protective layer.
It realizes crack suppression of extremely thin polarizers during heating while maintaining excellent optical performance, and is suitable for flexible and foldable display devices.
Smart Images

Figure 2025038087000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate, a polarizing plate with a retardation layer, and an image display device. [Background technology]
[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), have rapidly become widespread. In image display devices, a polarizing plate and a retardation plate, each of which includes a polarizer and a protective layer for protecting the polarizer, are usually used. In practice, a polarizing plate with a retardation layer, which is an integrated polarizing plate and a retardation plate, is widely used (e.g., Patent Document 1). Recently, with an increasing demand for thinner image display devices, there has been an increasing demand for thinner polarizing plates and polarizing plates with a retardation layer.
[0003] As a method for making a polarizing plate thinner, there have been proposed a method for reducing the thickness of a protective layer and a method for laminating a protective layer only on one side of a polarizer, but these methods have a problem that the polarizer cannot be sufficiently protected and is prone to cracking due to heating. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-210474 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a polarizing plate which, despite being very thin, is suppressed from cracking due to heating. [Means for solving the problem]
[0006] According to one aspect of the present invention, there is provided a polarizing plate having a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer arranged on one side of the polarizer, in which the polarizer satisfies the following formula (1) when the single transmittance of the polarizer is x% and the birefringence of the polyvinyl alcohol-based resin is y, and the protective layer is composed of a resin film having a thickness of 10 μm or less. y<-0.011x+0.525 (1) According to one aspect of the present invention, there is provided a polarizing plate having a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer arranged on one side of the polarizer, wherein the polarizer satisfies the following formula (2) when its single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film is z nm, and the protective layer is composed of a resin film having a thickness of 10 μm or less. z<-60x+2875 (2) According to one aspect of the present invention, there is provided a polarizing plate having a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer arranged on one side of the polarizer, wherein the polarizer satisfies the following formula (3) when the single transmittance of the polarizer is x% and the orientation function of the polyvinyl alcohol-based resin is f, and the protective layer is composed of a resin film having a thickness of 10 μm or less. f<-0.018x+1.11 (3) According to one aspect of the present invention, there is provided a polarizing plate having a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer disposed on one side of the polarizer, wherein the polarizer has a piercing strength of 30 gf / μm or more and the protective layer is composed of a resin film having a thickness of 10 μm or less. In one embodiment, the resin film contains at least one resin selected from an epoxy resin, a (meth)acrylic resin, a polyester resin, and a polyurethane resin. In one embodiment, the resin film is made of a photocationically cured epoxy resin, and the softening temperature of the resin film is 100° C. or higher. In one embodiment, the resin film is made of a solidified coating of an organic solvent solution of an epoxy resin, and the softening temperature of the resin film is 100° C. or higher. In one embodiment, the resin film is formed from a solidified coating of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, and the softening temperature of the resin film is 100° C. or higher. In one embodiment, the thermoplastic (meth)acrylic resin has at least one selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit. In one embodiment, the protective layer has an iodine adsorption amount of 25% by weight or less. In one embodiment, the polarizer has a thickness of 10 μm or less. In one embodiment, the polarizing plate is wound into a roll. According to another aspect of the present invention, the liquid crystal display device includes the polarizing plate and a retardation layer, the retardation layer being disposed on the side of the polarizer opposite to the side on which the protective layer is disposed. In one embodiment, the retardation layer is laminated on the polarizing plate via a pressure-sensitive adhesive layer. In one embodiment, the retardation layer has Re(550) of 100 nm to 190 nm, Re(450) / Re(550) is 0.8 or more and less than 1, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°. According to another aspect of the present invention, there is provided an image display device comprising the above polarizing plate or the retardation layer-attached polarizing plate. Effect of the Invention
[0007] According to the polarizing plate of the present invention, by adopting a polarizer in which the orientation state of the polyvinyl alcohol (PVA) resin is controlled, even if an extremely thin resin film is used as a protective layer, the occurrence of cracks during heating can be suppressed. Moreover, since such a polarizer can exhibit practically acceptable optical properties, the polarizing plate of the present invention can achieve both practically acceptable optical properties and suppression of the occurrence of cracks during heating, despite being very thin. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a drying shrinkage treatment using a heating roll in the production of a polarizer. [Diagram 3] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Figure 4] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 5] FIG. 2 is a diagram showing the relationship between the single transmittance of a polarizer and the birefringence of a PVA-based resin used in Examples and Comparative Examples. [Figure 6] FIG. 2 is a graph showing the relationship between the single transmittance of a polarizer and the in-plane retardation of a PVA-based resin film used in Examples and Comparative Examples. [Figure 7] FIG. 2 is a graph showing the relationship between the single transmittance of the polarizer and the orientation function of the PVA-based resin used in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments. In addition, each embodiment can be appropriately combined.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0011] A. Polarizing plate A-1. Overview of polarizing plates FIG. 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. The polarizing plate 100 of the illustrated example has a polarizer 10, a first protective layer 20 arranged on one side of the polarizer 10, and a second protective layer 30 arranged on the other side. The polarizer 10 is composed of a polyvinyl alcohol-based resin film containing a dichroic material. The first protective layer 20 is composed of a resin film having a thickness of 10 μm or less. The second protective layer 30 may be omitted depending on the purpose. Although not shown, a hard coat layer may be provided on the side of the first protective layer 20 opposite the polarizer 10 as necessary, and an easy-adhesion layer may be provided between the first protective layer 20 and the polarizer 10.
[0012] In one embodiment, the polarizer 10 satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin constituting the polarizer is y. In one embodiment, the polarizer 10 satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film constituting the polarizer is z nm. In one embodiment, the polarizer 10 satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. In one embodiment, the piercing strength of the polarizer is 30 gf / μm or more. y<-0.011x+0.525 (1) z<-60x+2875 (2) f< -0.018x+1.11 (3)
[0013] The total thickness of the polarizing plate 100 is, for example, 20 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less. The total thickness of the polarizing plate is, for example, 5 μm or more.
[0014] Each layer or optical film constituting the polarizing plate may be bonded via an adhesive layer, or may be formed in close contact without an adhesive layer. Examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. In the embodiment of the present invention, an adhesive layer can be suitably adopted. With such a configuration, the polarizing plate can be further thinned. Representative examples of the adhesive constituting the adhesive layer include an active energy ray curable adhesive (e.g., an ultraviolet ray curable adhesive).
[0015] In the embodiment of the present invention, the polarizing plate can be extremely thin. Therefore, it can be suitably applied to a flexible image display device. More preferably, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. Specific examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (e.g., an organic EL display device, an inorganic EL display device). Needless to say, the above description does not prevent the polarizing plate of the present invention from being applied to a normal image display device.
[0016] It is preferable that the polarizing plate has a very small change ΔTs in the single transmittance Ts and a very small change ΔP in the degree of polarization P after being left for 500 hours in an environment of 60° C. and 95% RH. The single transmittance Ts can be measured, for example, using a UV-Vis spectrophotometer (manufactured by JASCO Corporation, product name "V7100"). The degree of polarization P is calculated from the single transmittance (Ts), parallel transmittance (Tp), and cross transmittance (Tc) measured using the UV-Vis spectrophotometer according to the following formula. Degree of polarization (P)(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 The above Ts, Tp, and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Ts and P are essentially characteristics of a polarizer. ΔTs and ΔP are calculated by the following formulas. ΔTs(%)=Ts 500 -Ts 0 ΔP(%)=P 500 -P 0 Here, Ts 0 is the single unit transmittance before storage (initial stage), and Ts 500 is the single unit transmittance after standing, and P 0 is the degree of polarization before storage (initial state), and P 500is the degree of polarization after standing. ΔTs is preferably 3.0% or less, more preferably 2.5% or less, even more preferably 2.0% or less, and even more preferably 1.5% or less. ΔP is preferably -5.0% to 0%, more preferably -3.0% to 0%, even more preferably -1.0% to 0%, and even more preferably -0.5% to 0%.
[0017] The polarizing plate of the present invention may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape having a length that is sufficiently longer than the width, and includes, for example, a long and narrow shape having a length that is 10 times or more, preferably 20 times or more, larger than the width. A long and narrow polarizing plate can be wound into a roll.
[0018] A-2. Polarizer The polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material. In one embodiment, the polarizer satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin constituting the polarizer is y. In one embodiment, the polarizer satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film constituting the polarizer is z nm. In one embodiment, the polarizer satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. In one embodiment, the piercing strength of the polarizer is 30 gf / μm or more. y<-0.011x+0.525 (1) z<-60x+2875 (2) f<-0.018x+1.11 (3)
[0019] In a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic material, the birefringence of the PVA-based resin (hereinafter referred to as the birefringence of PVA or Δn of PVA), the in-plane retardation of the PVA-based resin film (hereinafter referred to as the in-plane retardation of PVA), the orientation function of the PVA-based resin (hereinafter referred to as the orientation function of PVA) and the piercing strength of the polarizer are all values related to the degree of orientation of the molecular chain of the PVA-based resin constituting the polarizer. Specifically, the birefringence, in-plane retardation and orientation function of PVA can become large with an increase in the degree of orientation, and the piercing strength can decrease with an increase in the degree of orientation. The polarizer used in the present invention (i.e., a polarizer satisfying the above formulas (1) to (3) or the piercing strength) is suppressed from thermally shrinking in the absorption axis direction due to the fact that the orientation of the molecular chain of the PVA-based resin in the absorption axis direction is gentler than that of conventional polarizers. As a result, a polarizing plate that is extremely thin yet suppresses the occurrence of cracks during heating can be obtained. In addition, since such a polarizer has excellent flexibility, a polarizing plate having excellent flexibility and bending durability can be obtained, and the polarizing plate can be preferably applied to a curved image display device, more preferably a bendable image display device, and even more preferably a foldable image display device. Conventionally, it has been difficult to obtain acceptable optical properties (typically, single transmittance and polarization degree) with a polarizer having a low degree of orientation, but the polarizer used in the present invention can achieve both a lower degree of orientation of the PVA-based resin than conventional ones and acceptable optical properties.
[0020] The polarizer preferably satisfies the following formula (1a) and / or formula (2a), and more preferably satisfies the following formula (1b) and / or formula (2b). -0.004x+0.18 <y<-0.011x+0.525 (1a) -0.003x+0.145 <y<-0.011x+0.520 (1b) -40x+1800 <z<-60x+2875 (2a) -30x+1450 <z<-60x+2850 (2b)
[0021] In this specification, the in-plane retardation of the PVA is the in-plane retardation value of the PVA-based resin film at 23° C. and a wavelength of 1000 nm. By using the near-infrared region as the measurement wavelength, it is possible to eliminate the influence of iodine absorption in the polarizer and to measure the retardation. In addition, the birefringence (in-plane birefringence) of the PVA is the value obtained by dividing the in-plane retardation of the PVA by the thickness (nm) of the polarizer.
[0022] The in-plane retardation of PVA is evaluated as follows: First, the retardation value is measured at multiple wavelengths of 850 nm or more, and the measured retardation value: R(λ) is plotted against the wavelength: λ, and this is fitted to the Sellmeier equation below by the least squares method. Here, A and B are fitting parameters and are coefficients determined by the least squares method. R(λ)=A+B / (λ 2 -600 2 ) In this case, the retardation value R(λ) can be separated into an in-plane retardation value (Rpva) of PVA that has no wavelength dependency and an in-plane retardation value (Ri) of iodine that has strong wavelength dependency, as shown below. Rpva= A Ri = B / (λ 2 -600 2 ) Based on this separation formula, the in-plane retardation (i.e., Rpva) of PVA at a wavelength λ=1000 nm can be calculated. The method for evaluating the in-plane retardation of PVA is also described in Japanese Patent No. 5932760, and can be referred to as necessary. In addition, the birefringence (Δn) of the PVA can be calculated by dividing this retardation by the thickness.
[0023] Examples of commercially available devices for measuring the in-plane retardation of PVA at a wavelength of 1000 nm include the KOBRA-WR / IR series and KOBRA-31X / IR series manufactured by Oji Measurement Co., Ltd.
[0024] The orientation function (f) of the polarizer used in the present invention preferably satisfies the following formula (3a), and more preferably satisfies the following formula (3b): If the orientation function is too small, an acceptable single-unit transmittance and / or degree of polarization may not be obtained. -0.01x+0.50 <f<-0.018x+1.11 (3a) -0.01x+0.57 <f<-0.018x+1.1 (3b)
[0025] The orientation function (f) is determined, for example, by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer (FT-IR) and polarized light as the measurement light. Specifically, germanium is used as the crystallite to which the polarizer is attached, the incident angle of the measurement light is 45°, the incident polarized infrared light (measurement light) is polarized light (s-polarized light) that vibrates parallel to the surface to which the germanium crystal sample is attached, and the measurement is performed with the stretch direction of the polarizer arranged parallel and perpendicular to the polarization direction of the measurement light. -1 The intensity I is calculated according to the following formula using the intensity of 3330 cm -1 is used as the reference peak, and 2941 cm -1 / 3330cm -1 The value is 2941 cm. Note that f=1 is perfect alignment, and f=0 is random. -1 The peak is due to the main chain (-CH) of PVA in the polarizer. 2 It is believed that this absorption is due to vibrations of the -. f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) however, c = (3cos 2 β-1) / 2, 2941cm -1 For vibration, β=90°. θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I⊥ ) / (I / / ) (In this case, the more the PVA molecules are oriented, the larger D becomes.) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel
[0026] The thickness of the polarizer is preferably 10 μm or less, and more preferably 8 μm or less. The lower limit of the thickness of the polarizer may be, for example, 1 μm. The thickness of the polarizer may be 2 μm to 10 μm in one embodiment, and 2 μm to 8 μm in another embodiment. By making the thickness of the polarizer so thin, it is possible to make the thermal shrinkage very small. It is presumed that such a configuration may also contribute to suppressing the occurrence of cracks due to heating.
[0027] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, more preferably 41.0% or more. The single transmittance can be, for example, 49.0% or less. In one embodiment, the single transmittance of the polarizer is 40.0% to 45.0%. The degree of polarization of the polarizer is preferably 99.0% or more, more preferably 99.4% or more. The degree of polarization can be, for example, 99.999% or less. In one embodiment, the degree of polarization of the polarizer is 99.0% to 99.99%. One of the features of the polarizer used in the present invention is that the degree of orientation of the PVA-based resin constituting the polarizer is lower than that of a conventional polarizer, and the polarizer has the above-mentioned in-plane retardation, birefringence, and / or orientation function, yet the polarizer can realize such a single transmittance and degree of polarization that are practically acceptable. This is presumably due to the manufacturing method described later. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The polarization degree is typically calculated by the following formula based on the parallel transmittance Tp and the crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0028] The piercing strength of the polarizer is, for example, 30 gf / μm or more, preferably 35 gf / μm or more, more preferably 40 gf / μm or more, even more preferably 45 gf / μm or more, and particularly preferably 50 gf / μm or more. The upper limit of the piercing strength can be, for example, 80 gf / μm. By setting the piercing strength of the polarizer in such a range, it is possible to significantly suppress the occurrence of cracks in the polarizer when heated and the polarizer from tearing along the absorption axis direction. As a result, a polarizer (and, as a result, a polarizing plate) with very excellent flexibility can be obtained. The piercing strength indicates the crack resistance of the polarizer when the polarizer is pierced with a predetermined strength. The piercing strength can be expressed, for example, as the strength (breaking strength) at which the polarizer breaks when a predetermined needle is attached to a compression tester and the needle is pierced into the polarizer at a predetermined speed. As is clear from the unit, the piercing strength means the piercing strength per unit thickness (1 μm) of the polarizer.
[0029] As described above, the polarizer is composed of a PVA-based resin film containing a dichroic material. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially the polarizer) contains an acetoacetyl-modified PVA-based resin. With such a configuration, a polarizer having a desired piercing strength can be obtained. The blending amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, when the entire PVA-based resin is taken as 100% by weight. If the blending amount is within such a range, the piercing strength can be set to a more suitable range.
[0030] A polarizer can be typically produced using a laminate of two or more layers. A specific example of a polarizer obtained using a laminate includes a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch the laminate. Furthermore, the stretching preferably further includes stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is preferably 3.0 to 4.5 times, which is significantly smaller than normal. Even at such a total stretching ratio, a polarizer having acceptable optical properties can be obtained by adding a halide and combining it with a dry shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the boric acid water stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even at a small total stretching ratio. In addition, the laminate is preferably subjected to a dry shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. In one embodiment, the method for producing a polarizer includes subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a dry shrinkage treatment in this order. By introducing the auxiliary stretching, even when a PVA-based resin is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA-based resin, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water in the subsequent dyeing and stretching processes can be prevented, making it possible to achieve high optical properties.Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing process and an underwater stretching process. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage process. The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate and any suitable protective layer may be laminated on the peeled surface according to the purpose. Details of the method for producing a polarizer will be described in detail in Section A-3.
[0031] A-3. Manufacturing method of polarizer A method for producing a polarizer according to one embodiment of the present invention includes forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a halide and a polyvinyl alcohol-based resin (PVA-based resin) on one side of a long thermoplastic resin substrate to form a laminate, and subjecting the laminate to an auxiliary air-stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order, in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 1% to 10% in the width direction. The content of the halide in the PVA-based resin layer is preferably 5 parts by weight to 20 parts by weight with respect to 100 parts by weight of the PVA-based resin. The drying shrinkage treatment is preferably performed using a heating roll, and the temperature of the heating roll is preferably 60° C. to 120° C. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 1% to 10%. According to such a production method, the polarizer described in the above item A-2 can be obtained. In particular, a laminate including a PVA-based resin layer containing a halide is prepared, the laminate is stretched in multiple stages including auxiliary air stretching and underwater stretching, and the laminate after stretching is heated with a heating roll, whereby a polarizer having excellent optical properties (typically, single transmittance and polarization degree) can be obtained.
[0032] A-3-1. Preparation of laminate Any suitable method can be adopted as a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer. Preferably, a coating liquid containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate, and then dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.
[0033] Any appropriate method can be used as the coating method of the coating liquid. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. are listed. The coating and drying temperature of the coating liquid is preferably 50° C. or higher.
[0034] The thickness of the PVA-based resin layer is preferably 2 μm to 30 μm, and more preferably 2 μm to 20 μm. By making the thickness of the PVA-based resin layer before stretching very thin in this manner and reducing the total stretching ratio as described later, a polarizer having an acceptable single transmittance and polarization degree can be obtained despite a very small orientation function.
[0035] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.
[0036] A-3-1-1. Thermoplastic resin base material Any suitable thermoplastic resin film may be used as the thermoplastic resin substrate. Details of the thermoplastic resin substrate are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455 A. The entire disclosure of these publications is incorporated herein by reference.
[0037] A-3-1-2. Coating solution The coating liquid contains a halide and a PVA resin as described above. The coating liquid is typically a solution in which the halide and the PVA resin are dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The concentration of the PVA resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.
[0038] Additives may be added to the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These can be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.
[0039] Any appropriate resin may be adopted as the PVA-based resin. Examples include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. By using a PVA-based resin having such a saponification degree, a polarizer having excellent durability can be obtained. If the saponification degree is too high, gelation may occur. As described above, the PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin.
[0040] The average degree of polymerization of the PVA resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.
[0041] Any suitable halide may be used as the halide. For example, iodide and sodium chloride may be used. For example, iodide may be potassium iodide, sodium iodide, and lithium iodide. Among these, potassium iodide is preferred.
[0042] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight per 100 parts by weight of the PVA-based resin. If the amount of the halide exceeds 20 parts by weight per 100 parts by weight of the PVA-based resin, the halide may bleed out, causing the finally obtained polarizer to become cloudy.
[0043] Generally, the orientation of polyvinyl alcohol molecules in the PVA-based resin layer increases when the PVA-based resin layer is stretched, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of polyvinyl alcohol molecules may be disturbed and the orientation may decrease. In particular, when a laminate of a thermoplastic resin substrate and a PVA-based resin layer is stretched in boric acid water, the tendency of the orientation degree to decrease is significant when the laminate is stretched in boric acid water at a relatively high temperature to stabilize the stretching of the thermoplastic resin substrate. For example, the stretching of a PVA film alone in boric acid water is generally performed at 60°C, whereas the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA-based resin layer is performed at a high temperature of about 70°C, in which case the orientation of PVA at the initial stage of stretching may decrease before it increases due to underwater stretching. In response to this, a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate is prepared, and the laminate is stretched at high temperature (auxiliary stretching) in air before being stretched in boric acid water, so that the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a process such as a dyeing process and an underwater stretching process.
[0044] A-3-2. Aerial supplementary stretching process In particular, in order to obtain high optical properties, a two-stage stretching method is selected, which combines dry stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching like two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when applying a PVA-based resin on a thermoplastic resin substrate, it is necessary to lower the application temperature compared to when applying a PVA-based resin on a normal metal drum in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, and as a result, the crystallization of the PVA-based resin becomes relatively low, and a problem that sufficient optical properties cannot be obtained may occur. On the other hand, by introducing auxiliary stretching, it is possible to increase the crystallinity of the PVA-based resin even when applying a PVA-based resin on a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution can be prevented when immersed in water in the subsequent dyeing process or stretching process, and it is possible to achieve high optical properties.
[0045] The stretching method of the auxiliary air stretching may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or free end stretching (for example, a method of uniaxially stretching the laminate through rolls having different peripheral speeds). In order to obtain high optical properties, free end stretching may be actively adopted. In one embodiment, the air stretching process includes a heated roll stretching process in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. The air stretching process typically includes a zone stretching process and a heated roll stretching process. The order of the zone stretching process and the heated roll stretching process is not limited, and the zone stretching process may be performed first, or the heated roll stretching process may be performed first. The zone stretching process may be omitted. In one embodiment, the zone stretching process and the heated roll stretching process are performed in this order. In another embodiment, the film is stretched by gripping the film end in a tenter stretching machine and widening the distance between the tenters in the flow direction (the widening of the distance between the tenters is the stretching ratio). At this time, the distance of the tenter in the width direction (perpendicular to the machine direction) is set to be as close as possible. Preferably, it can be set to be as close as possible to the free end stretching ratio in the machine direction. In the case of free end stretching, the shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.
[0046] The auxiliary air-drawing may be performed in one step or in multiple steps. When the auxiliary air-drawing is performed in multiple steps, the draw ratio is the product of the draw ratios in each step. The draw direction in the auxiliary air-drawing is preferably approximately the same as the draw direction in the underwater drawing.
[0047] The stretching ratio in the auxiliary air stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. If the stretching ratio of the auxiliary air stretching is in such a range, the total stretching ratio can be set in a desired range when combined with underwater stretching, and a desired orientation function can be realized. As a result, a polarizer in which crack generation due to heating is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even if the total stretching ratio is small. More specifically, the ratio of the stretching ratio of the auxiliary air stretching to the stretching ratio of the underwater stretching (underwater stretching / auxiliary air stretching) is preferably 0.4 to 0.9, more preferably 0.5 to 0.8.
[0048] The stretching temperature of the auxiliary in-air stretching can be set to any appropriate value depending on the material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate + 10°C, and particularly preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA resin can be suppressed, and defects due to the crystallization (for example, the orientation of the PVA resin layer due to stretching is hindered) can be suppressed.
[0049] A-3-3. Insolubilization, dyeing and crosslinking treatments If necessary, after the auxiliary air stretching treatment, an insolubilization treatment is performed before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). If necessary, after the dyeing treatment, a crosslinking treatment is performed before the underwater stretching treatment. The crosslinking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described, for example, in JP 2012-73580 A (above).
[0050] A-3-4. Underwater stretching treatment The underwater stretching treatment is performed by immersing the laminate in a stretching bath. According to the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched while suppressing crystallization. As a result, a polarizer having excellent optical properties can be produced.
[0051] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing multiple stages, the total stretching ratio is the product of the stretching ratios in each stage.
[0052] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as a stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and to produce a polarizer with excellent optical properties.
[0053] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizer with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.
[0054] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.
[0055] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, the laminate can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a risk that the substrate cannot be stretched well even when the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0056] The stretching ratio in underwater stretching is preferably 1.0 to 2.2 times, more preferably 1.1 to 2.0 times, further preferably 1.1 to 1.8 times, and further more preferably 1.2 to 1.6 times. When the stretching ratio in underwater stretching is in such a range, the total stretching ratio can be set in a desired range, and the desired birefringence, in-plane retardation, and / or orientation function can be realized. As a result, a polarizer in which the occurrence of cracks due to heating is suppressed can be obtained. As described above, the total stretching ratio (the total stretching ratio when the auxiliary air stretching and the underwater stretching are combined) is preferably 3.0 to 4.5 times, more preferably 3.0 to 4.3 times, and further preferably 3.0 to 4.0 times, relative to the original length of the laminate. By appropriately combining the addition of a halide to the coating solution, the adjustment of the stretching ratios of the auxiliary air stretching and the underwater stretching, and the drying shrinkage treatment, a polarizer having acceptable optical properties can be obtained even at such a total stretching ratio.
[0057] A-3-5. Drying shrinkage treatment The drying shrinkage treatment may be performed by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll) (heat roll drying method). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce a polarizer with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also the occurrence of wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because the orientation of the PVA and the PVA / iodine complex can be effectively increased. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.
[0058] 2 is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 50 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rolls R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 50 (for example, the thermoplastic resin substrate surface).
[0059] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and an optical laminate with extremely excellent durability can be produced. The temperature of the heating rolls can be measured by a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular restriction as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.
[0060] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.
[0061] A-3-6. Other processing Preferably, after the underwater stretching treatment and before the drying shrinkage treatment, a washing treatment is carried out. The washing treatment is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.
[0062] A-4. First protective layer The thickness of the first protective layer is 10 μm or less. The thickness of the first protective layer is 10 μm or less, which can contribute to the thinning of the polarizing plate. Conventionally, a protective layer having a thickness of 20 μm or more has been used in order to protect the polarizer by following the shrinkage of the polarizer when heated. In contrast, the polarizer used in the embodiment of the present invention has a lower degree of orientation of the PVA resin than conventional polarizers as described above, and as a result, shrinkage due to heating is small, so that even when a protective layer having a thickness of 10 μm or less is used, the occurrence of cracks during heating is suppressed.
[0063] The thickness of the first protective layer is preferably 7 μm or less, more preferably 5 μm or less, and further preferably 3 μm or less. The thickness of the first protective layer is, for example, 1 μm or more.
[0064] The first protective layer is composed of a resin film. As the resin forming the resin film, any appropriate resin may be used depending on the purpose. Specific examples include thermoplastic resins such as (meth)acrylic, cellulose such as triacetyl cellulose (TAC), polyester, polyurethane, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, and acetate; thermosetting resins or active energy ray curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone; and glassy polymers such as siloxane polymers. In one embodiment, at least one resin selected from epoxy resins, (meth)acrylic resins, polyester resins, and urethane resins is used as the resin forming the resin film.
[0065] The resin film constituting the first protective layer may be, for example, a molded product of a molten resin, or a solidified product of a coating film of a resin solution obtained by dissolving or dispersing a resin in an aqueous solvent or an organic solvent, or a cured product of a curable resin (for example, a photocationically cured product).
[0066] In one embodiment, the first protective layer is composed of at least one selected from the group consisting of a solidified coating film of an organic solvent solution of a thermoplastic (meth)acrylic resin (hereinafter, the (meth)acrylic resin may be simply referred to as an "acrylic resin"), a photocationically cured product of an epoxy resin, and a solidified coating film of an organic solvent solution of an epoxy resin. This will be specifically described below.
[0067] A-4-1.Solidified coating of organic solvent solution of thermoplastic acrylic resin In one embodiment, the first protective layer is composed of a solidified coating film of a solution of a thermoplastic acrylic resin in an organic solvent. The softening temperature of the first protective layer in this embodiment is preferably 100° C. or higher, more preferably 115° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher from the viewpoint of humidification durability, and is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower from the viewpoint of moldability.
[0068] A-4-1-1. Acrylic resin The acrylic resin preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the first protective layer is also approximately 100° C. or higher. If the Tg of the acrylic resin is 100° C. or higher, a polarizing plate including a protective layer obtained from such a resin can have excellent humidification durability in addition to crack resistance. The Tg of the acrylic resin is more preferably 110° C. or higher, even more preferably 115° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the acrylic resin is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the acrylic resin is in such a range, it can have excellent moldability.
[0069] As the acrylic resin, any appropriate acrylic resin may be adopted as long as it has the above Tg. The acrylic resin typically contains an alkyl(meth)acrylate as a main component as a monomer unit (repeating unit). In this specification, "(meth)acrylic" means acrylic and / or methacrylic. Examples of the alkyl(meth)acrylate constituting the main skeleton of the acrylic resin include linear or branched alkyl groups having 1 to 18 carbon atoms. These can be used alone or in combination. Furthermore, any appropriate copolymerization monomer may be introduced into the acrylic resin by copolymerization. The repeating unit derived from the alkyl(meth)acrylate is typically represented by the following general formula (1):
[0070] [ka]
[0071] In the general formula (1), R 4 represents a hydrogen atom or a methyl group, and R 5represents a hydrogen atom, or an optionally substituted aliphatic or alicyclic hydrocarbon group having 1 to 6 carbon atoms. Examples of the substituent include halogen and a hydroxyl group. Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, and methyl 2-(hydroxyethyl)acrylate. In the general formula (1), R 5 is preferably a hydrogen atom or a methyl group. Thus, a particularly preferred alkyl (meth)acrylate is methyl acrylate or methyl methacrylate.
[0072] The acrylic resin may contain only a single alkyl (meth)acrylate unit, or may be a single alkyl (meth)acrylate unit represented by the general formula (1) above. 4 and R 5 It may contain a plurality of alkyl (meth)acrylate units having different structures.
[0073] The content of alkyl (meth)acrylate units in the acrylic resin is preferably 50 mol% to 98 mol%, more preferably 55 mol% to 98 mol%, even more preferably 60 mol% to 98 mol%, particularly preferably 65 mol% to 98 mol%, and most preferably 70 mol% to 97 mol%. If the content is less than 50 mol%, the effects derived from the alkyl (meth)acrylate units (e.g., high heat resistance, high transparency) may not be fully exhibited. If the content is more than 98 mol%, the resin may become brittle and easily cracked, and high mechanical strength may not be fully exhibited, resulting in poor productivity.
[0074] The acrylic resin preferably has a repeating unit containing a ring structure. Examples of the repeating unit containing a ring structure include a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit containing a ring structure may contain only one type of repeating unit, or may contain two or more types of repeating units.
[0075] The lactone ring unit is preferably represented by the following general formula (2):
[0076] [ka] In the general formula (2), R 1 , R 2 and R 3 each independently represents a hydrogen atom or an organic residue having 1 to 20 carbon atoms. The organic residue may contain an oxygen atom. The acrylic resin may contain only a single lactone ring unit, and R 1 , R 2 and R 3 The acrylic resin may contain a plurality of lactone ring units having different ring structures. Acrylic resins having lactone ring units are described in, for example, JP-A-2008-181078, the disclosure of which is incorporated herein by reference.
[0077] The glutarimide unit is preferably represented by the following general formula (3):
[0078] [ka]
[0079] In the general formula (3), R 11 and R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms; R 13 represents hydrogen, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 11 and R 12 are each independently a hydrogen atom or a methyl group, and R 13 is hydrogen, a methyl group, a butyl group, or a cyclohexyl group. More preferably, R 11 is a methyl group, and R 12 is hydrogen, and R 13 is a methyl group. The acrylic resin may contain only a single glutarimide unit, and R 11 , R 12 and R 13 Acrylic resins having glutarimide units may contain a plurality of glutarimide units having different groups. Examples of acrylic resins having glutarimide units are described in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, and JP-A-2006-337569, the disclosures of which are incorporated herein by reference. Note that the glutaric anhydride unit is represented by the formula (3) above, 13 The above description regarding the glutarimide unit applies, except that the nitrogen atom substituted with is an oxygen atom.
[0080] As for the maleic anhydride unit and the maleimide (N-substituted maleimide) unit, their structures are specified from their names, and therefore specific explanations are omitted.
[0081] The content of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and even more preferably 20 mol% to 30 mol%. If the content is too low, Tg may be less than 100°C, and the heat resistance, solvent resistance, and surface hardness of the resulting protective layer may be insufficient. If the content is too high, moldability and transparency may be insufficient.
[0082] The acrylic resin may contain repeating units other than the alkyl (meth)acrylate unit and the repeating unit containing a ring structure. Examples of such repeating units include repeating units derived from vinyl monomers copolymerizable with the monomers constituting the above units (other vinyl monomer units). Examples of other vinyl monomers include acrylic acid, methacrylic acid, crotonic acid, 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, acrylonitrile, methacrylonitrile, ethacrylonitrile, allyl glycidyl ether, maleic anhydride, itaconic anhydride, N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide, aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminoethyl methacrylate, ethylaminopropyl methacrylate, cyclohexylaminoethyl methacrylate, N-vinyldiethylamine, N-acetylvinylamine, allylamine, methallylamine, N-methylallylamine, 2-isopropenyl-oxazoline, 2-vinyl-oxazoline, 2-acroyl-oxazoline, N-phenylmaleimide, phenylaminoethyl methacrylate, styrene, α-methylstyrene, p-glycidylstyrene, p-aminostyrene, and 2-styryl-oxazoline. These may be used alone or in combination. The type, number, combination, content ratio, etc. of the other vinyl monomer units may be appropriately set depending on the purpose.
[0083] The weight average molecular weight of the acrylic resin is preferably 1000 to 2000000, more preferably 5000 to 1000000, further preferably 10000 to 500000, particularly preferably 50000 to 500000, and most preferably 60000 to 150000. The weight average molecular weight can be determined, for example, using a gel permeation chromatograph (GPC system, manufactured by Tosoh Corporation) in terms of polystyrene. Tetrahydrofuran can be used as the solvent.
[0084] The acrylic resin can be polymerized by any suitable polymerization method using an appropriate combination of the above monomer units.
[0085] In the embodiment of the present invention, the acrylic resin may be used in combination with other resins. That is, the monomer components constituting the acrylic resin may be copolymerized with the monomer components constituting the other resins, and the copolymer may be used to form the protective layer described below; a blend of the acrylic resin and the other resin may be used to form the protective layer. Examples of the other resins include thermoplastic resins such as styrene resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide. The type and amount of the resin used in combination may be appropriately set depending on the purpose and the properties desired for the resulting film. For example, a styrene resin (preferably, an acrylonitrile-styrene copolymer) may be used in combination as a retardation control agent.
[0086] The content of the acrylic resin in the first protective layer of the present embodiment is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the high heat resistance and high transparency inherent to the acrylic resin may not be fully exhibited.
[0087] The first protective layer of the present embodiment can be formed, for example, by applying a solution of an acrylic resin in an organic solvent onto the surface of a polarizer to form a coating film, and then solidifying the coating film.
[0088] As the organic solvent, any suitable organic solvent capable of dissolving or uniformly dispersing the acrylic resin can be used. Specific examples of the organic solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.
[0089] The concentration of the acrylic resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the polarizer can be formed.
[0090] The solution may be applied to any suitable substrate or to a polarizer. When the solution is applied to a substrate, the solidified coating film formed on the substrate is transferred to the polarizer. When the solution is applied to a polarizer, the coating film is dried (solidified) to form a first protective layer directly on the polarizer. Preferably, the solution is applied to a polarizer, and the first protective layer is formed directly on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. Any suitable method can be adopted as a method for applying the solution. Specific examples include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.).
[0091] The first protective layer can be formed by drying (solidifying) the coating film of the solution. The drying temperature is preferably 100° C. or lower, and more preferably 50° C. to 70° C. If the drying temperature is within this range, adverse effects on the polarizer can be prevented. The drying time can vary depending on the drying temperature. The drying time can be, for example, 1 minute to 10 minutes.
[0092] A-4-2. Photo-cured epoxy resin In one embodiment, the first protective layer is composed of a photocationically cured product of an epoxy resin. By using such a protective layer, the occurrence of cracks can be suppressed and excellent humidification durability can be obtained. As described above, since the first protective layer is a photocationically cured product, the composition for forming a protective layer contains a photocationic polymerization initiator. The photocationic polymerization initiator is a photosensitive agent having a function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. Ring-opening polymerization of epoxy groups proceeds due to the acid generated from this photocationic polymerization initiator. The first protective layer, which is a photocationically cured product obtained, has a high softening temperature and can have a reduced amount of iodine adsorption. Therefore, it is possible to provide a polarizing plate that is suppressed from occurring cracks and has excellent humidification durability.
[0093] The softening temperature of the first protective layer in this embodiment is, from the viewpoint of humid durability, preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, and particularly preferably 125°C or higher, and from the viewpoint of formability, is preferably 300°C or lower, more preferably 250°C or lower, even more preferably 200°C or lower, and particularly preferably 160°C or lower.
[0094] A-4-2-1.Epoxy resin Any suitable epoxy resin can be used as the epoxy resin, and an epoxy resin having an aromatic ring or an alicyclic ring can be preferably used. In this embodiment, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton can be preferably used. Examples of the aromatic skeleton include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. Preferably, an epoxy resin having a biphenyl skeleton or a bisphenol skeleton as the aromatic skeleton, or a hydrogenated product thereof, is used. By using such an epoxy resin, a polarizing plate having better durability and excellent flexibility can be provided. Hereinafter, an epoxy resin having a biphenyl skeleton will be described in detail as a representative example.
[0095] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having the following structure: The epoxy resin having a biphenyl skeleton may be used alone or in combination of two or more kinds. [ka] (In the formula, R 14 ~R 21 each independently represents a hydrogen atom, a linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, or a halogen element).
[0096] R 14 ~R 21each independently represents a hydrogen atom, a linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, or a halogen element. Examples of linear or branched, substituted or unsubstituted hydrocarbon groups having 1 to 12 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, a cyclododecyl group, a phenyl group, a benzyl group, a methylbenzyl group, a dimethylbenzyl group, a trimethylbenzyl group, a naphthylmethyl group, a phenethyl group, and a 2-phenylisopropyl group. The linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms preferably includes an alkyl group having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, etc. The halogen element preferably includes fluorine and bromine.
[0097] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin represented by the following formula: [ka] (In the formula, R 14 ~R 21 is as above, and n represents an integer of 0 to 6).
[0098] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having only a biphenyl skeleton. By using an epoxy resin having only a biphenyl skeleton, the durability of the obtained protective layer can be further improved.
[0099] In one embodiment, the epoxy resin having a biphenyl skeleton may contain a chemical structure other than the biphenyl skeleton. Examples of the chemical structure other than the biphenyl skeleton include a bisphenol skeleton, an alicyclic structure, and an aromatic ring structure. In this embodiment, the proportion (molar ratio) of the chemical structure other than the biphenyl skeleton is preferably smaller than that of the biphenyl skeleton.
[0100] The epoxy resin having a biphenyl skeleton may be a commercially available product, such as those manufactured by Mitsubishi Chemical Corporation under the trade names jER YX4000, jER YX4000H, jER YL6121, jER YL664, jER YL6677, jER YL6810, and jER YL7399.
[0101] The epoxy resin (epoxy resin after photocationic curing) preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the protective layer is also approximately 100° C. or higher. If the Tg of the epoxy resin is 100° C. or higher, the polarizing plate including the obtained protective layer is likely to have excellent durability. The Tg of the epoxy resin is more preferably 110° C. or higher, further preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the epoxy resin is preferably 300° C. or lower, more preferably 250° C. or lower, further preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the epoxy resin is within such a range, excellent moldability can be obtained.
[0102] The epoxy equivalent of the epoxy resin is preferably 100 g / equivalent or more, more preferably 150 g / equivalent or more, and even more preferably 200 g / equivalent or more. The epoxy equivalent of the epoxy resin is preferably 3000 g / equivalent or less, more preferably 2500 g / equivalent or less, and even more preferably 2000 g / equivalent or less. By setting the epoxy equivalent within the above range, a more stable protective layer (a protective layer with less residual monomer and sufficiently cured) can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy group" and can be measured in accordance with JIS K7236.
[0103] In this embodiment, the epoxy resin may be used in combination with other resins. That is, a blend of the epoxy resin (for example, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton) with other resins may be used to form the protective layer. Examples of the other resins include thermoplastic resins such as styrene-based resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide, and curable resins such as acrylic resins and oxetane resins. Preferably, acrylic resins and oxetane resins are used. The type and amount of the resin used in combination can be appropriately set depending on the purpose and the properties desired for the resulting film. For example, a styrene-based resin can be used in combination as a retardation control agent.
[0104] Any suitable (meth)acrylic compound can be used as the acrylic resin. For example, the (meth)acrylic compound includes, for example, a (meth)acrylic compound having one (meth)acryloyl group in the molecule (hereinafter also referred to as a "monofunctional (meth)acrylic compound") and a (meth)acrylic compound having two or more (meth)acryloyl groups in the molecule (hereinafter also referred to as a "polyfunctional (meth)acrylic compound"). These (meth)acrylic compounds may be used alone or in combination of two or more. These acrylic resins are described, for example, in JP 2019-168500 A. The entire disclosure of this publication is incorporated herein by reference.
[0105] As the oxetane resin, any suitable compound having one or more oxetanyl groups in the molecule can be used. Examples of the oxetane compounds include oxetane compounds having one oxetanyl group in the molecule, such as 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, and (3-ethyloxetan-3-yl)methyl (meth)acrylate; and oxetane compounds having two or more oxetanyl groups in the molecule, such as 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl. These oxetane resins may be used alone or in combination of two or more.
[0106] As the oxetane resin, preferably used are 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, etc. These oxetane resins are easily available and can have excellent dilution properties (low viscosity) and compatibility.
[0107] In one embodiment, from the viewpoint of compatibility and adhesiveness, an oxetane resin having a molecular weight of 500 or less and being liquid at room temperature (25° C.) is used. In one embodiment, an oxetane compound containing two or more oxetanyl groups in the molecule, an oxetane compound containing one oxetanyl group and one (meth)acryloyl group or one epoxy group in the molecule is preferably used, and more preferably 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, or (3-ethyloxetan-3-yl)methyl (meth)acrylate is used. By using these oxetane resins, the curability and durability of the protective layer can be improved.
[0108] As the oxetane resin, a commercially available product may be used. Specifically, ARON OXT-101, ARON OXT-121, ARON OXT-212, and ARON OXT-221 (all manufactured by Toagosei Co., Ltd.) may be used. Preferably, ARON OXT-101 and ARON OXT-221 may be used.
[0109] The content of the epoxy resin (for example, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton) in the first protective layer of the present embodiment is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the protective layer may not have sufficient heat resistance and adhesion to the polarizer.
[0110] When an epoxy resin having a biphenyl skeleton or a bisphenol skeleton is used in combination with an oxetane resin, the content of the oxetane resin is preferably 1 to 50 parts by weight, more preferably 5 to 45 parts by weight, and even more preferably 10 to 40 parts by weight, relative to 100 parts by weight of the total amount of the epoxy resin and the oxetane resin. By setting the content within the above range, the curability is improved, and the adhesion between the protective layer and the polarizer can also be improved.
[0111] A-4-2-2. Photocationic polymerization initiator The photocationic polymerization initiator is a photosensitive agent having the function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. The acid generated from this photocationic polymerization initiator causes ring-opening polymerization of the epoxy group. As the photocationic polymerization initiator, any suitable compound that can cure an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton by irradiation with light such as ultraviolet light can be used. Only one type of photocationic polymerization initiator may be used, or two or more types may be used in combination.
[0112] Examples of the photocationic polymerization initiator include triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, p-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate, p-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluoroantimonate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluorophosphate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluoroantimonate, (2,4-cyclopentadiene-1-yl)[(1-methylethyl)benzene]-Fe-hexafluorophosphate, and diphenyliodonium hexafluoroantimonate. Preferably, a triphenylsulfonium salt-based hexafluoroantimonate type photocationic polymerization initiator or a diphenyliodonium salt-based hexafluoroantimonate type photocationic polymerization initiator is used.
[0113] The photocationic polymerization initiator may be a commercially available product, such as triphenylsulfonium salt-based hexafluoroantimonate type SP-170 (manufactured by ADEKA Corporation), CPI-101A (manufactured by San-Apro Corporation), WPAG-1056 (manufactured by Wako Pure Chemical Industries, Ltd.), diphenyliodonium salt-based hexafluoroantimonate type WPI-116 (manufactured by Wako Pure Chemical Industries, Ltd.), etc.
[0114] The content of the cationic photopolymerization initiator is preferably 0.1 to 3 parts by weight, more preferably 0.25 to 2 parts by weight, relative to 100 parts by weight of the epoxy resin (for example, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton). If the content of the cationic photopolymerization initiator is less than 0.1 part by weight, the resin may not be sufficiently cured even when irradiated with light (ultraviolet rays).
[0115] The first protective layer of the present embodiment can be formed, for example, by applying a composition containing the above-mentioned epoxy resin and a photocationic polymerization initiator to form a coating film, and then irradiating the coating film with light (e.g., ultraviolet light).
[0116] The solvent contained in the composition may be any suitable solvent capable of dissolving or uniformly dispersing the epoxy resin and the curing agent. Specific examples of the solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.
[0117] The epoxy resin concentration in the composition is preferably 10 parts by weight to 30 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that adheres closely to the polarizer can be formed.
[0118] The composition may be applied to any suitable substrate or to a polarizer. When the composition is applied to a substrate, the cured product of the coating film formed on the substrate is transferred to the polarizer. When the composition is applied to a polarizer, the coating film is cured, for example, by light irradiation, to directly form a first protective layer on the polarizer. Preferably, the composition is applied to a polarizer, and a first protective layer is directly formed on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. The method of applying the composition is as described above.
[0119] When the coating film is cured by light irradiation, the coating film can be irradiated with light (typically ultraviolet light) using any appropriate light source so as to have any appropriate irradiation amount. Examples of the ultraviolet light source that can be used include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, electrodeless lamps, carbon arc lamps, xenon lamps, metal halide lamps, chemical lamps, black lights, LED lamps, etc. The irradiation amount of ultraviolet light is, for example, 2 mJ / cm. 2 ~3000mJ / cm 2 , preferably 10 mJ / cm 2 ~2000mJ / cm2 Specifically, when a high-pressure mercury lamp is used as the light source, the irradiation dose is usually 5 mJ / cm 2 ~3000mJ / cm 2 , preferably 50 mJ / cm 2 ~2000mJ / cm 2 When using an electrodeless lamp as the light source, the irradiation dose is usually 2 mJ / cm 2 ~2000mJ / cm 2 , preferably 10 mJ / cm 2 ~1000mJ / cm 2 This is carried out under the following conditions.
[0120] The irradiation time can be set to any appropriate value depending on the type of light source, the distance between the light source and the coating surface, the coating thickness, and other conditions. The irradiation time is usually several seconds to several tens of seconds, and may be a fraction of a second. The light can be irradiated from any appropriate direction. In order to prevent non-uniform curing, it is preferable to irradiate from the coating surface side of the composition for forming a protective layer.
[0121] After exposure to light such as ultraviolet light, a heat treatment may be further carried out to complete the curing by photoreaction. The heat treatment may be carried out at any appropriate temperature and time. The heating temperature is, for example, 80°C to 250°C, and preferably 100°C to 150°C. The heating time is, for example, 10 seconds to 2 hours, and preferably 5 minutes to 1 hour.
[0122] A-4-3.Solidified coating of epoxy resin in organic solvent solution In one embodiment, the first protective layer is composed of a solidified coating film of an organic solvent solution of an epoxy resin. The softening temperature of the first protective layer in this embodiment is preferably 100° C. or higher, more preferably 110° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher, from the viewpoint of humidification durability, and is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower, from the viewpoint of moldability.
[0123] A-4-3-1.Epoxy resin In this embodiment, the epoxy resin preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the protective layer is also approximately 100° C. or higher. If the Tg of the epoxy resin is 100° C. or higher, a polarizing plate including a protective layer obtained from such a resin is likely to have excellent durability. The Tg of the epoxy resin is more preferably 110° C. or higher, further preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the epoxy resin is preferably 300° C. or lower, more preferably 250° C. or lower, further preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the epoxy resin is within such a range, it can have excellent moldability.
[0124] As the epoxy resin, any suitable epoxy resin may be adopted as long as it has the above-mentioned Tg. The epoxy resin typically refers to a resin having an epoxy group in its molecular structure. As the epoxy resin, an epoxy resin having an aromatic ring in its molecular structure is preferably used. By using an epoxy resin having an aromatic ring, an epoxy resin having a higher Tg can be obtained. Examples of the aromatic ring in the epoxy resin having an aromatic ring in its molecular structure include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. When two or more types of epoxy resins are used, an epoxy resin having an aromatic ring and an epoxy resin not having an aromatic ring may be used in combination.
[0125] Specific examples of epoxy resins having an aromatic ring in the molecular structure include bisphenol A diglycidyl ether type epoxy resins, bisphenol F diglycidyl ether type epoxy resins, bisphenol S diglycidyl ether type epoxy resins, resorcinol diglycidyl ether type epoxy resins, hydroquinone diglycidyl ether type epoxy resins, terephthalic acid diglycidyl ester type epoxy resins, bisphenoxyethanol fluorene diglycidyl ether type epoxy resins, bisphenol fluorene diglycidyl ether type epoxy resins, and biscresol fluorene diglycidyl ether type epoxy resins. Examples of epoxy resins include epoxy resins having two epoxy groups such as phenol-type epoxy resins; epoxy resins having three epoxy groups such as novolac-type epoxy resins, N,N,O-triglycidyl-P- or -m-aminophenol-type epoxy resins, N,N,O-triglycidyl-4-amino-m- or -5-amino-o-cresol-type epoxy resins, and 1,1,1-(triglycidyloxyphenyl)methane-type epoxy resins; and epoxy resins having four epoxy groups such as glycidylamine-type epoxy resins (e.g., diaminodiphenylmethane type, diaminodiphenylsulfone type, and metaxylenediamine type). In addition, glycidyl ester-type epoxy resins such as hexahydrophthalic anhydride-type epoxy resins, tetrahydrophthalic anhydride-type epoxy resins, dimer acid-type epoxy resins, and p-oxybenzoic acid-type epoxy resins may also be used.
[0126] The weight average molecular weight of the epoxy resin is preferably 1000 to 2000000, more preferably 5000 to 1000000, further preferably 10000 to 500000, particularly preferably 50000 to 500000, and most preferably 60000 to 150000. The weight average molecular weight can be determined, for example, using a gel permeation chromatograph (GPC system, manufactured by Tosoh Corporation) in terms of polystyrene. Tetrahydrofuran can be used as the solvent.
[0127] The epoxy equivalent of the epoxy resin is preferably 1000 g / equivalent or more, more preferably 3000 g / equivalent or more, and even more preferably 5000 g / equivalent or more. The epoxy equivalent of the epoxy resin is preferably 30000 g / equivalent or less, more preferably 25000 g / equivalent or less, and even more preferably 20000 g / equivalent or less. By setting the epoxy equivalent within the above range, a more stable protective layer can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy groups" and can be measured in accordance with JIS K7236.
[0128] In this embodiment, the epoxy resin may be used in combination with other resins. That is, a blend of the epoxy resin and other resins may be used to form the protective layer. Examples of the other resins include thermoplastic resins such as styrene-based resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide. The type and amount of the resin used in combination may be appropriately set depending on the purpose and the properties desired for the resulting film. For example, the styrene-based resin may be used in combination as a retardation control agent.
[0129] The content of the epoxy resin in the first protective layer of the present embodiment is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the protective layer may not have sufficient heat resistance and adhesion to the polarizer.
[0130] The first protective layer of the present embodiment can be formed, for example, by applying an organic solvent solution containing the epoxy resin to form a coating film, and then solidifying the coating film. The epoxy resin concentration in the organic solvent solution is preferably 3 parts by weight to 20 parts by weight per 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the polarizer can be formed.
[0131] As the organic solvent, any suitable solvent capable of dissolving or uniformly dispersing the epoxy resin can be used. Specific examples of the solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.
[0132] The solution may be applied to any suitable substrate or to a polarizer. When the solution is applied to a substrate, the solidified coating film formed on the substrate is transferred to the polarizer. When the solution is applied to a polarizer, the coating film is dried (solidified) to form a first protective layer directly on the polarizer. Preferably, the solution is applied to a polarizer, and the first protective layer is formed directly on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. The method of applying the solution is as described above.
[0133] By drying (solidifying) the coating film of the solution, a protective layer, which is a solidified coating film, can be formed. The drying temperature is preferably 100° C. or lower, and more preferably 50° C. to 70° C. If the drying temperature is within this range, adverse effects on the polarizer can be prevented. The drying time can vary depending on the drying temperature. The drying time can be, for example, 1 minute to 10 minutes.
[0134] A-4-4. Composition and characteristics of protective layer In one embodiment, the first protective layer is composed of at least one selected from the group consisting of a solidified coating film of an organic solvent solution of a thermoplastic acrylic resin, a photocationically cured product of an epoxy resin, and a solidified coating film of an organic solvent solution of an epoxy resin, as described above. Such a protective layer can be made significantly thinner than an extrusion-molded film. The thickness of the first protective layer is 10 μm or less, as described above. Although not theoretically clear, such a protective layer has the advantages of being smaller in shrinkage during film molding than cured products of other thermosetting resins or active energy ray-curable resins (e.g., ultraviolet-curable resins), and being free of residual monomers, etc., suppressing deterioration of the film itself, and suppressing adverse effects on the polarizing plate (polarizer) caused by residual monomers, etc. Furthermore, it has the advantage of being excellent in humidification durability because it has smaller hygroscopicity and moisture permeability than solidified products of aqueous coating films such as aqueous solutions or aqueous dispersions. As a result, a polarizing plate with excellent durability that can maintain optical properties even under a heated and humidified environment can be realized.
[0135] The first protective layer is preferably substantially optically isotropic. In this specification, "substantially optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the thickness direction retardation Rth(550) is -20 nm to +10 nm. The in-plane retardation Re(550) is more preferably 0 nm to 5 nm, further preferably 0 nm to 3 nm, and particularly preferably 0 nm to 2 nm. The thickness direction retardation Rth(550) is more preferably -5 nm to +5 nm, further preferably -3 nm to +3 nm, and particularly preferably -2 nm to +2 nm. If the Re(550) and Rth(550) of the first protective layer are within such ranges, adverse effects on the display characteristics can be prevented when a polarizing plate including the protective layer is applied to an image display device.
[0136] The higher the light transmittance at 380 nm for the first protective layer with a thickness of 3 μm, the more preferable. Specifically, the light transmittance is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. If the light transmittance is within this range, the desired transparency can be ensured. The light transmittance can be measured, for example, by a method conforming to ASTM-D-1003.
[0137] The lower the haze of the first protective layer, the better. Specifically, the haze is preferably 5% or less, more preferably 3% or less, even more preferably 1.5% or less, and particularly preferably 1% or less. When the haze is 5% or less, the film can be given a good sense of clarity. Furthermore, even when used as a polarizing plate on the viewing side of an image display device, the displayed content can be viewed well.
[0138] The YI of the first protective layer at a thickness of 3 μm is preferably 1.27 or less, more preferably 1.25 or less, even more preferably 1.23 or less, and particularly preferably 1.20 or less. If the YI exceeds 1.3, the optical transparency may be insufficient. The YI can be calculated by the following formula from the tristimulus values (X, Y, Z) of the color obtained by measurement using a high-speed integrating sphere type spectral transmittance measuring device (product name DOT-3C: manufactured by Murakami Color Research Laboratory). YI = [(1.28X-1.06Z) / Y] x 100
[0139] The b value (a measure of hue according to the Hunter color system) of the first protective layer at a thickness of 3 μm is preferably less than 1.5, more preferably 1.0 or less. If the b value is 1.5 or more, an undesired color tone may appear. The b value can be obtained, for example, by cutting a sample of the film constituting the protective layer into a 3 cm square, measuring the hue using a high-speed integrating sphere type spectral transmittance measuring device (product name DOT-3C: manufactured by Murakami Color Research Laboratory), and evaluating the hue according to the Hunter color system.
[0140] The iodine adsorption amount of the first protective layer is preferably 25% by weight or less, more preferably 10% by weight or less, even more preferably 6.0% by weight or less, and particularly preferably 3.0% by weight or less. The smaller the iodine adsorption amount, the more preferable. If the iodine adsorption amount is within such a range, a polarizing plate having even better durability can be obtained. The iodine adsorption amount can be measured by the following method. A protective layer (thickness 3 μm) is formed on the substrate (PET film) to obtain a PET film with a protective layer. The obtained PET film with a protective layer is cut into a size of 1 cm × 1 cm (1 cm 2 ) was cut out as a sample and placed in a headspace vial (20 mL capacity) and weighed. Next, a screw cap vial (1.5 mL capacity) containing 1 mL of iodine solution was also placed in this headspace vial and sealed. The headspace vial was then placed in a dryer at 65°C and heated for 6 hours to allow the sample to become iodine-containing in the gaseous state. 2 The iodine is then adsorbed. The sample is then placed in a ceramic boat and burned using an automatic sample combustion device, and the generated gas is collected in 10 mL of absorption liquid. After collection, this absorption liquid is adjusted to 15 mL with pure water, and either the original solution or an appropriately diluted solution is subjected to IC quantitative analysis. Note that when a similar measurement is performed using only the PET film, the amount of iodine adsorption is nearly zero. The amount of iodine adsorption (wt%) is calculated from the weight of iodine obtained by IC quantitative analysis and the weight of the protective layer alone ("weight of PET film with protective layer" - "weight of PET film") using the following formula. Iodine adsorption amount (wt%) = weight of iodine obtained by IC quantitative analysis / weight of protective layer alone × 100 For the analysis, for example, the following measuring devices can be used. [Measuring equipment] Automatic sample combustion device: Mitsubishi Chemical Analytech Co., Ltd., "AQF-2100H" IC (anion): Thermo Fisher Scientific, "ICS-3000"
[0141] The first protective layer (for example, a solidified product of a coating film or a photocationically cured product) may contain any suitable additive depending on the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic or inorganic fillers; resin modifiers; organic or inorganic fillers; plasticizers; lubricants; antistatic agents; and flame retardants. The additives may be added during polymerization of the resin or during formation of the protective layer. The type, number, combination, and amount of additives may be appropriately set depending on the purpose.
[0142] A-5. Second protective layer In one embodiment, the second protective layer is formed of any appropriate film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. The thickness of the second protective layer in this embodiment is preferably 5 μm to 80 μm, more preferably 5 μm to 40 μm, and even more preferably 5 μm to 25 μm.
[0143] In another embodiment, the second protective layer may be a solidified coating of a resin solution, or may be a cured product of a curable resin (e.g., a photocationically cured product). The same explanation as for the first protective layer can be applied to the second protective layer of this embodiment.
[0144] A-6. Other layers An easy-adhesion layer may be formed on the polarizer side of the protective layer (typically, the first protective layer). The easy-adhesion layer contains, for example, a water-based polyurethane and an oxazoline-based crosslinking agent. By forming such an easy-adhesion layer, the adhesion between the protective layer and the polarizer can be increased. In addition, a hard coat layer may be formed on the side of the protective layer (typically, the first protective layer) opposite to the polarizer. In addition, when a hard coat layer is formed, the hard coat layer may be formed so that the total thickness of the protective layer (for example, the solidified product of the coating film) and the hard coat layer is 10 μm or less, preferably 7 μm or less, and more preferably 5 μm or less. The hard coat layer may be formed on the viewing side of the viewing-side protective layer. In the case where both the easy-adhesion layer and the hard coat layer are formed, typically, they may be formed on different sides of the protective layer.
[0145] B. Polarizing plate with retardation layer B-1. Overall structure of polarizing plate with retardation layer FIG. 3 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 200a of this embodiment has a polarizing plate 100 having a polarizer 10 and a first protective layer 20 arranged on one side thereof, and a retardation layer 110 arranged on the side of the polarizer 10 opposite to the side on which the first protective layer 20 is arranged. In the retardation layer-attached polarizing plate 200a, the retardation layer 110 can also function as a protective layer for the polarizer 10. The retardation layer 110 is typically laminated on the polarizing plate 100 via an adhesive layer (not shown). The adhesive layer is an adhesive layer or a pressure-sensitive adhesive layer, and is preferably a pressure-sensitive adhesive layer (for example, an acrylic pressure-sensitive adhesive layer) from the viewpoint of reworkability and the like. Although not shown, the polarizing plate 100 may have a second protective layer on the retardation layer 110 side of the polarizer 10 as necessary.
[0146] As shown in FIG. 4, in the retardation layer-attached polarizing plate 200b according to another embodiment, another retardation layer 120 and / or a conductive layer or a conductive layer-attached isotropic substrate 130 may be provided. The other retardation layer 120 and the conductive layer or the conductive layer-attached isotropic substrate 130 are typically provided on the outside of the retardation layer 110 (the opposite side to the polarizing plate 100). The other retardation layer 120 typically exhibits a refractive index characteristic of nz>nx=ny. The other retardation layer 120 and the conductive layer or the conductive layer-attached isotropic substrate 130 are typically provided in this order from the retardation layer 110 side. The other retardation layer 120 and the conductive layer or the conductive layer-attached isotropic substrate 130 are typically any layers provided as necessary, and either one or both may be omitted. For convenience, the retardation layer 110 may be referred to as a first retardation layer, and the other retardation layer 120 may be referred to as a second retardation layer. In addition, when a conductive layer or an isotropic substrate with a conductive layer is provided, the polarizing plate with a retardation layer can be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizing plate.
[0147] In the embodiment of the present invention, Re(550) of the first retardation layer 110 is preferably 100 nm to 190 nm, and Re(450) / Re(550) is preferably 0.8 or more and less than 1. Furthermore, typically, the angle between the slow axis of the first retardation layer 110 and the absorption axis of the polarizer 10 is 40° to 50°.
[0148] The above embodiments may be appropriately combined, and the components in the above embodiments may be modified as is obvious in the art. For example, the configuration in which the conductive layer-attached isotropic base material 130 is provided on the outside of the second retardation layer 120 may be replaced with an optically equivalent configuration (for example, a laminate of the second retardation layer and a conductive layer).
[0149] The polarizing plate with a retardation layer according to the embodiment of the present invention may further include other retardation layers. The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers can be appropriately set according to the purpose.
[0150] B-2. Polarizing plate The polarizing plate 100 is the polarizing plate described in Item A.
[0151] B-3. First retardation layer The first retardation layer 110 may have any suitable optical and / or mechanical properties according to the purpose. The first retardation layer typically has a slow axis. In one embodiment, the angle θ formed by the slow axis of the first retardation layer and the absorption axis of the polarizer 10 is 40° to 50° as described above, preferably 42° to 48°, and more preferably about 45°. If the angle θ is within such a range, by using the first retardation layer as a λ / 4 plate as described later, a polarizing plate with retardation layer having very excellent circular polarization characteristics (and as a result, very excellent antireflection characteristics) can be obtained.
[0152] The first retardation layer preferably exhibits a refractive index characteristic of nx > ny ≧ nz. The first retardation layer is typically provided to impart antireflection characteristics to the polarizing plate and can function as a λ / 4 plate in one embodiment. In this case, the in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range that does not impair the effects of the present invention, ny < nz may occur.
[0153] The Nz coefficient of the first retardation layer is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained polarizing plate with retardation layer is used in an image display device, a very excellent reflected hue can be achieved.
[0154] The first retardation layer may exhibit a reverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value hardly changes according to the wavelength of the measurement light. In one embodiment, the first retardation layer exhibits a reverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, it is possible to realize very excellent antireflection properties.
[0155] The absolute value of the photoelastic coefficient of the first retardation layer is preferably 2×10 -11 m 2 / N or less, preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, and more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 If the absolute value of the photoelastic coefficient is within this range, the retardation is unlikely to change even when shrinkage stress occurs during heating. As a result, the thermal unevenness of the resulting image display device can be effectively prevented.
[0156] The first retardation layer is typically made of a stretched resin film. In one embodiment, the thickness of the first retardation layer is preferably 70 μm or less, more preferably 45 μm to 60 μm. If the thickness of the first retardation layer is in such a range, curling during heating can be well suppressed and curling during lamination can be well adjusted. In addition, in an embodiment in which the first retardation layer is made of a polycarbonate-based resin film as described below, the thickness of the first retardation layer is preferably 40 μm or less, more preferably 10 μm to 40 μm, and further preferably 20 μm to 30 μm. By making the first retardation layer of a polycarbonate-based resin film having such a thickness, it is possible to suppress curling and contribute to improving bending durability and reflection hue.
[0157] The first retardation layer may be made of any suitable resin film that satisfies the above characteristics. Representative examples of such resins include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blended or copolymerized). When the first retardation layer is made of a resin film that exhibits reverse dispersion wavelength characteristics, polycarbonate-based resins or polyester carbonate-based resins (hereinafter may be simply referred to as polycarbonate-based resins) may be suitably used.
[0158] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used in the present invention are described, for example, in JP-A-2014-10291, JP-A-2014-26266, JP-A-2015-212816, JP-A-2015-212817, and JP-A-2015-212818, and these descriptions are incorporated herein by reference.
[0159] The glass transition temperature of the polycarbonate resin is preferably 110°C or higher and 150°C or lower, more preferably 120°C or higher and 140°C or lower. If the glass transition temperature is too low, the heat resistance tends to be poor, and dimensional changes may occur after film formation, and the image quality of the obtained organic EL panel may be reduced. If the glass transition temperature is too high, the forming stability during film formation may be poor, and the transparency of the film may be impaired. The glass transition temperature is determined in accordance with JIS K 7121 (1987).
[0160] The molecular weight of the polycarbonate resin can be expressed by reduced viscosity. The reduced viscosity is measured using methylene chloride as a solvent, a polycarbonate concentration precisely adjusted to 0.6 g / dL, and a temperature of 20.0°C ± 0.1°C using an Ubbelohde viscometer. The lower limit of the reduced viscosity is usually preferably 0.30 dL / g, more preferably 0.35 dL / g or more. The upper limit of the reduced viscosity is usually preferably 1.20 dL / g, more preferably 1.00 dL / g, and even more preferably 0.80 dL / g. If the reduced viscosity is smaller than the lower limit, the mechanical strength of the molded product may be reduced. On the other hand, if the reduced viscosity is larger than the upper limit, the flowability during molding may be reduced, and problems such as reduced productivity and moldability may occur.
[0161] A commercially available film may be used as the polycarbonate-based resin film. Specific examples of commercially available products include "Pure Ace WR-S", "Pure Ace WR-W", and "Pure Ace WR-M" manufactured by Teijin Limited, and "NRF" manufactured by Nitto Denko Corporation.
[0162] The first retardation layer is obtained, for example, by stretching a film formed from the polycarbonate-based resin. Any appropriate molding method can be adopted as a method for forming a film from a polycarbonate-based resin. Specific examples include compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP molding, cast coating (for example, casting), calendar molding, and heat pressing. The extrusion molding method or cast coating method is preferred. This is because it can increase the smoothness of the obtained film and obtain good optical uniformity. The molding conditions can be appropriately set according to the composition and type of the resin used, the properties desired for the retardation layer, and the like. As mentioned above, many film products of polycarbonate-based resins are commercially available, so the commercially available film may be directly subjected to the stretching treatment.
[0163] The thickness of the resin film (unstretched film) can be set to any appropriate value depending on the desired thickness of the first retardation layer, the desired optical properties, the stretching conditions described below, etc. It is preferably 50 μm to 300 μm.
[0164] The stretching may be performed by any suitable stretching method and condition (e.g., stretching temperature, stretching ratio, stretching direction). Specifically, various stretching methods such as free end stretching, fixed end stretching, free end shrinkage, fixed end shrinkage, etc. may be used alone, simultaneously, or sequentially. Stretching may be performed in various directions or dimensions such as the length direction, width direction, thickness direction, and oblique direction. The stretching temperature is preferably Tg-30°C to Tg+60°C relative to the glass transition temperature (Tg) of the resin film, and more preferably Tg-10°C to Tg+50°C.
[0165] By appropriately selecting the above-mentioned stretching method and stretching conditions, a retardation film having the above-mentioned desired optical properties (for example, refractive index properties, in-plane retardation, Nz coefficient) can be obtained.
[0166] In one embodiment, the retardation film is produced by uniaxially stretching or fixed-end uniaxially stretching a resin film. A specific example of fixed-end uniaxial stretching is a method of stretching a resin film in the width direction (lateral direction) while running the resin film in the longitudinal direction. The stretching ratio is preferably 1.1 to 3.5 times.
[0167] In another embodiment, the retardation film can be produced by continuously obliquely stretching a long resin film in the direction of the above angle θ with respect to the longitudinal direction. By employing oblique stretching, a long stretched film having an orientation angle of angle θ with respect to the longitudinal direction of the film (slow axis in the direction of angle θ) can be obtained, and for example, roll-to-roll lamination with a polarizer is possible, and the manufacturing process can be simplified. The angle θ can be the angle formed by the absorption axis of the polarizer and the slow axis of the retardation layer in the retardation layer-attached polarizing plate. As described above, the angle θ is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°.
[0168] An example of a stretching machine used for oblique stretching is a tenter type stretching machine capable of applying a feeding force, a pulling force, or a take-up force at different speeds in the transverse and / or longitudinal directions. Tenter type stretching machines include a transverse uniaxial stretching machine and a simultaneous biaxial stretching machine, and any appropriate stretching machine can be used as long as it can continuously obliquely stretch a long resin film.
[0169] By appropriately controlling the left and right speeds in the stretching machine, respectively, a retardation layer (essentially, a long retardation film) having the desired in-plane retardation and a slow axis in the desired direction can be obtained.
[0170] The stretching temperature of the film may vary depending on the in-plane retardation value and thickness desired for the retardation layer, the type of resin used, the thickness of the film used, the stretching ratio, etc. Specifically, the stretching temperature is preferably Tg-30°C to Tg+30°C, more preferably Tg-15°C to Tg+15°C, and most preferably Tg-10°C to Tg+10°C. By stretching at such a temperature, a first retardation layer having suitable properties in the present invention can be obtained. Note that Tg is the glass transition temperature of the constituent material of the film.
[0171] B-4. Second retardation layer As described above, the second retardation layer may be a so-called positive C plate whose refractive index characteristics show the relationship nz>nx=ny. By using a positive C plate as the second retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the thickness direction retardation Rth(550) of the second retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second retardation layer may be less than 10 nm.
[0172] The second retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The second retardation layer is preferably made of a film containing a liquid crystal material fixed in a homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0173] B-5. Conductive layer or isotropic substrate with conductive layer The conductive layer can be formed by forming a metal oxide film on any suitable substrate by any suitable film forming method (e.g., vacuum deposition, sputtering, CVD, ion plating, spraying, etc.). Examples of metal oxides include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, and indium-zinc composite oxide. Among these, indium-tin composite oxide (ITO) is preferred.
[0174] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.
[0175] The conductive layer may be transferred from the substrate to the first retardation layer (or the second retardation layer, if present) and used alone as a constituent layer of the retardation layer-attached polarizing plate, or may be laminated with the substrate (substrate with conductive layer) to the first retardation layer (or the second retardation layer, if present). Preferably, the substrate is optically isotropic, and therefore the conductive layer can be used in the retardation layer-attached polarizing plate as an isotropic substrate with conductive layer.
[0176] Any suitable isotropic substrate may be used as the optically isotropic substrate (isotropic substrate). Examples of materials constituting the isotropic substrate include materials having a resin without a conjugated system, such as norbornene-based resins and olefin-based resins, as the main skeleton, and materials having a ring structure, such as a lactone ring or a glutarimide ring, in the main chain of an acrylic resin. When such materials are used, the occurrence of retardation due to the orientation of molecular chains can be suppressed when the isotropic substrate is formed. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.
[0177] The conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer may be patterned as necessary. By patterning, a conductive portion and an insulating portion may be formed. As a result, an electrode may be formed. The electrode may function as a touch sensor electrode that senses contact with the touch panel. Any appropriate method may be adopted as the patterning method. Specific examples of the patterning method include a wet etching method and a screen printing method.
[0178] C. Image display device The polarizing plate or the retardation layer-attached polarizing plate can be applied to an image display device. Therefore, the present invention includes an image display device including the polarizing plate or the retardation layer-attached polarizing plate. Representative examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (for example, an organic EL display device, an inorganic EL display device). The image display device according to the embodiment of the present invention includes the polarizing plate described in the above item A or the retardation layer-attached polarizing plate described in the above item B on the viewing side. The retardation layer-attached polarizing plate is laminated so that the retardation layer is on the image display cell (for example, a liquid crystal cell, an organic EL cell, an inorganic EL cell) side (so that the polarizer is on the viewing side). In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. In such an image display device, the effect of the retardation layer-attached polarizing plate of the present invention becomes remarkable. EXAMPLES
[0179] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0180] (1) Thickness The thickness of the polarizer was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"). The calculated wavelength range used for thickness calculation was 400 nm to 500 nm, and the refractive index was 1.53. The thickness of the protective layer was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"), with the calculated wavelength range and refractive index appropriately selected. The thickness of the easy-adhesion layer was obtained by observation with a scanning electron microscope (SEM). Thicknesses exceeding 10 μm were measured using a digital micrometer (Anritsu Co., Ltd., product name "KC-351C"). (2) Orientation function of PVA For the polarizer (single polarizer) obtained by peeling off the resin substrate from the laminate of polarizer / thermoplastic resin substrate used in the examples and comparative examples, a Fourier transform infrared spectrophotometer (FT-IR) (manufactured by Perkin Elmer, product name: "Frontier") was used to measure attenuated total reflection (ATR) spectroscopy of the polarizer surface on the surface opposite to the surface on which the resin substrate was peeled off, using polarized infrared light as the measurement light. Germanium was used as the crystallite to which the polarizer was attached, and the angle of incidence of the measurement light was 45°. The orientation function was calculated by the following procedure. The polarized infrared light (measurement light) to be incident was polarized light (s-polarized light) that vibrated parallel to the surface to which the germanium crystal sample was attached, and the absorbance spectrum of each was measured with the stretching direction of the polarizer arranged perpendicular (⊥) and parallel ( / / ) to the polarization direction of the measurement light. From the obtained absorbance spectrum, (3330 cm -1 Intensity) was used as a reference (2941 cm -1 The intensity I was calculated. ⊥ is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged perpendicular (⊥) to the polarization direction of the measurement light (2941 cm-1 strength) / (3330cm -1 In addition, I / / is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged parallel ( / / ) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 Intensity), where (2941 cm -1 Intensity) is the bottom of the absorbance spectrum, 2770 cm -1 and 2990cm -1 2941cm when using this as the baseline -1 is the absorbance of (3330cm -1 Strength) is 2990cm -1 and 3650cm -1 3330cm when the baseline is -1 The absorbance of the obtained I ⊥ and I / / The orientation function f was calculated according to formula 1. Note that f = 1 is perfect orientation, and f = 0 is random. -1 The peak is due to the main chain (-CH) of PVA in the polarizer. 2 -) vibration-induced absorption. -1 The peak is said to be due to the vibration of the hydroxyl group of PVA. (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] however c = (3cos 2 β-1) / 2 So, as mentioned above, 2941cm -1 When using, β=90°⇒f=-2×(1-D) / (2D+1). θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel (3) In-plane retardation of PVA (Re) For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the in-plane retardation (Rpva) of PVA at a wavelength of 1000 nm was evaluated using a retardation measurement device (manufactured by Oji Scientific Instruments, product name "KOBRA-31X100 / IR") (this is the value obtained by subtracting the in-plane retardation (Ri) of iodine from the total in-plane retardation at a wavelength of 1000 nm according to the principle explained above). The absorption edge wavelength was set to 600 nm. (4) Birefringence of PVA (Δn) The birefringence (Δn) of the PVA was calculated by dividing the in-plane retardation of the PVA measured in (3) above by the thickness of the polarizer. (5) Piercing strength The polarizer was peeled off from the laminate of polarizer / resin substrate used in the examples and comparative examples, and placed on a compression tester (manufactured by Kato Tech, product name "NDG5" needle penetration force measurement specifications) equipped with a needle, and pierced at a piercing speed of 0.33 cm / sec under a room temperature (23°C ± 3°C) environment. The strength at which the polarizer broke was taken as the breaking strength (piercing strength). The evaluation value was the average value of the breaking strengths of 10 sample pieces. The needle used had a tip diameter of 1 mmφ and 0.5R. The polarizer to be measured was fixed by clamping both sides of the polarizer with a jig having a circular opening with a diameter of about 11 mm, and the needle was pierced into the center of the opening to perform the test. (6) Cracks The polarizing plate or the polarizing plate with a retardation layer obtained in the examples and comparative examples was cut into a size of 100 mm x 100 mm. The cut sample was attached to a glass plate (thickness 1.1 mm) via an acrylic adhesive layer with a thickness of 15 μm so that the protective layer was on the outside. The sample attached to the glass plate was placed in an oven at 85°C for 120 hours, and then visually confirmed whether or not cracks occurred in the absorption axis direction (MD direction) of the polarizer. This evaluation was performed using three polarizing plates with a retardation layer, and a plate with at least one crack was evaluated as "occurred", and a plate with no cracks was evaluated as "absent". (7) Single unit transmittance and polarization degree For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc were measured using an ultraviolet-visible spectrophotometer (JASCO Corporation, "V-7100"). These Ts, Tp, and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The polarization degree P was calculated from the obtained Tp and Tc using the following formula. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 It should be noted that equivalent measurements can also be made using a spectrophotometer such as the Otsuka Electronics LPF-200, and it has been confirmed that equivalent measurement results can be obtained regardless of which spectrophotometer is used. (8) Humidification durability From the polarizing plate or the polarizing plate with retardation layer obtained in the examples and comparative examples, a test piece (50 mm x 50 mm) was cut out with two sides perpendicular to the absorption axis direction of the polarizer and the absorption axis direction facing each other. The test piece was attached to an alkali-free glass plate with an adhesive so that the protective layer was on the outside to obtain a test sample. The test sample was measured for the single transmittance (Ts), parallel transmittance (Tp) and crossed transmittance (Tc) using an ultraviolet-visible spectrophotometer (manufactured by JASCO Corporation, product name "V7100") in the same manner as in (7), and the polarization degree (P) was obtained. At this time, the measurement light was incident from the protective layer side. Next, the test sample was left in an oven at 60°C and 95% RH for 500 hours to heat and humidify it (humid heat test), and the polarization degree P 0 and the polarization degree P after the heat and humidity test 500 From this, the change in the degree of polarization ΔP was calculated using the following formula. ΔP(%)=P 500 -P 0 The obtained ΔP results were evaluated according to the following criteria. Good: ΔP is -5.0% to 0% Defective: ΔP is less than -5.0% or color loss occurs (9) Softening temperature of protective layer In the same manner as in the formation of the protective layer in each of the Examples and Comparative Examples, a protective layer (thickness: 3 μm) was formed on one side of the polarizer (total stretch ratio: 5.5 times) produced in Comparative Example 1. A local thermal analysis (nano TA measurement) was performed on the protective layer surface of the resulting polarizing plate [protective layer / polarizer], and the softening temperature of the protective layer was calculated. The measurement device and measurement conditions are as follows. Measurement device: Hitachi High-Tech Science, product name "AFM5300E / / Nano-TA2" Measurement mode: Contact mode Probe: AN2-200 Measurement area: 8μm □ scan Measurement atmosphere: atmospheric pressure (10) Iodine adsorption A protective layer (thickness: 3 μm) was formed on one side of the PET film in the same manner as in the formation of the protective layer in each of the Examples and Comparative Examples. The obtained PET film with the protective layer was cut into a size of 1 cm × 1 cm (1 cm 2 ) was cut out as a sample and collected in a headspace vial (volume 20 mL) and weighed. Next, a screw tube bottle (volume 1.5 mL) containing 1 mL of iodine solution (iodine concentration 1 wt %, potassium iodide concentration 7 wt %) was also placed in this headspace vial and sealed. The headspace vial was then placed in a dryer at 65°C and heated for 6 hours (this allowed the gaseous I 2 (Iodine is adsorbed by the sample). The sample was then placed in a ceramic boat and burned using an automatic sample combustion device, and the generated gas was collected in 10 mL of absorption liquid. After collection, this absorption liquid was adjusted to 15 mL with pure water, and IC quantitative analysis was performed on the original solution or on a solution that had been appropriately diluted. Note that, since the amount of iodine adsorption was nearly zero when a similar measurement was performed on the PET film alone, the amount of iodine adsorption (wt%) was calculated from the weight of iodine obtained by IC quantitative analysis and the weight of the protective layer alone ("weight of PET film with protective layer" - "weight of PET film") using the following formula: Iodine adsorption amount (wt%) = weight of iodine obtained by IC quantitative analysis / weight of protective layer alone × 100 The measuring device is as follows. [Measuring equipment] Automatic sample combustion device: Mitsubishi Chemical Analytech Co., Ltd., "AQF-2100H" IC (anion): Thermo Fisher Scientific, "ICS-3000"
[0181] [Example 1-1] 1. Preparation of a laminate of polarizer / resin substrate The resin substrate was a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, product name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizer would be 41.5% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4.0% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) by 1.46 times between rolls with different peripheral speeds (underwater stretching process) (as a result, the total stretching ratio was 2.4 × 1.46 = 3.5 times). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for about 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. In this manner, a polarizer having a thickness of 6.7 μm was formed on the resin substrate, and a laminate of the polarizer and the resin substrate was produced. 0 is 41.5%, and the degree of polarization (initial degree of polarization) P 0 was 99.99%.
[0182] 2. Formation of an easy-to-adhere layer A polyurethane-based water-dispersible resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Superflex SF210) was applied to a thickness of 0.1 μm on the polarizer surface of the obtained laminate to form an easy-adhesion layer.
[0183] 3. Preparation of Protective Layer 20 parts by weight of an acrylic resin (Kusumoto Chemicals, product name: B-728) which is 100% polymethyl methacrylate was dissolved in 80 parts by weight of methyl ethyl ketone to obtain an acrylic resin solution (20%). This acrylic resin solution was applied to the surface of the easy-adhesion layer of the laminate obtained above using a wire bar, and the coating film was dried at 60°C for 5 minutes to form a protective layer constituted as a solidified coating film. The thickness of the protective layer was 3 μm. Next, the resin substrate was peeled off from the obtained laminate to obtain a polarizing plate having a configuration of protective layer (solidified coating film) / easy-adhesion layer / polarizer.
[0184] [Example 1-2] A polarizing plate having a structure of hard coat layer / protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-1, except that the thickness of the protective layer was set to 2 μm and a hard coat layer (thickness 3 μm) was further formed on the surface of the protective layer opposite the easy-adhesion layer. The hard coat layer was prepared by mixing 70 parts by weight of dimethylol-tricyclodecane diacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate DCP-A), 20 parts by weight of isobornyl acrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate IB-XA), 10 parts by weight of 1,9-nonanediol diacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate 1.9NA-A), and 3 parts by weight of a photopolymerization initiator (BASF Co., Ltd., product name: Irgacure 907) using an appropriate solvent, and applying the resulting coating liquid onto the protective layer surface so as to have a thickness of 3 μm after curing. The solvent was then dried, and the coating was applied to the protective layer using a high-pressure mercury lamp with an integrated light dose of 300 mJ / cm. 2 The film was formed by irradiating ultraviolet light under a nitrogen atmosphere so as to obtain a film having a thickness of 100 nm.
[0185] [Examples 1-3] A polarizing plate having a hard coat layer / protective layer (solidified coating film) / easy adhesion layer / polarizer structure was obtained in the same manner as in Example 1-1, except that an acrylic resin having a lactone ring unit, which is polymethyl methacrylate (lactone ring unit 30 mol%), was used instead of the acrylic resin having a 100% polymethyl methacrylate, the thickness of the protective layer was set to 2 μm, and a hard coat layer (thickness 3 μm) was further formed on the surface of the protective layer opposite to the easy adhesion layer. The hard coat layer was formed in the same manner as in Example 1-2.
[0186] [Examples 1-4] A polarizing plate having a hard coat layer / protective layer (solidified coating film) / easy adhesion layer / polarizer structure was obtained in the same manner as in Example 1-1, except that an acrylic resin having a glutarimide ring unit (4 mol% glutarimide ring unit) was used instead of an acrylic resin having a 100% polymethyl methacrylate, the thickness of the protective layer was set to 2 μm, and a hard coat layer (3 μm thick) was further formed on the surface of the protective layer opposite to the easy adhesion layer. The hard coat layer was formed in the same manner as in Example 1-2.
[0187] [Examples 1-5] A polarizing plate having a structure of protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-1, except that an acrylic resin which is a copolymer of methyl methacrylate / butyl methacrylate (molar ratio 80 / 20) was used instead of the acrylic resin which is 100% polymethyl methacrylate.
[0188] [Examples 1-6] A polarizing plate having a hard coat layer / protective layer (solidified coating film) / easy adhesion layer / polarizer structure was obtained in the same manner as in Example 1-1, except that an acrylic resin that is a copolymer of methyl methacrylate / butyl methacrylate (molar ratio 80 / 20) was used instead of the acrylic resin that is 100% polymethyl methacrylate, the thickness of the protective layer was set to 2 μm, and a hard coat layer (thickness 3 μm) was further formed on the surface of the protective layer opposite to the easy adhesion layer. The hard coat layer was formed in the same manner as in Example 1-2.
[0189] [Examples 1-7] A polarizing plate having a structure of protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-1, except that an acrylic resin which is a copolymer of methyl methacrylate / ethyl acrylate (molar ratio 55 / 45) (manufactured by Kusumoto Chemical Industries, product name "B-722") was used instead of the acrylic resin which is 100% polymethyl methacrylate.
[0190] [Examples 1-8] A polarizing plate having a configuration of protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-1, except that an acrylic resin which is a copolymer of methyl methacrylate / butyl methacrylate (molar ratio 35 / 65) (manufactured by Kusumoto Chemical Industries, product name "B-734") was used instead of the acrylic resin which is 100% polymethyl methacrylate.
[0191] [Example 2-1] 1. Preparation of a laminate of polarizer / resin substrate In the same manner as in Example 1-1, a polarizer having a thickness of 6.7 μm was formed on a resin substrate to prepare a laminate of the polarizer and the resin substrate. 2. Preparation of the Protective Layer 15 parts of an epoxy resin having a biphenyl skeleton (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX4000) was dissolved in 83.8 parts of methyl ethyl ketone to obtain an epoxy resin solution. 1.2 parts of a photocationic polymerization initiator (manufactured by San-Apro Co., Ltd., product name: CPI (registered trademark)-100P) was added to the obtained epoxy resin solution to obtain a protective layer forming composition. The obtained protective layer forming composition was directly applied to the polarizer surface (i.e., without forming an easy-adhesion layer) using a wire bar, and the coating film was dried at 60°C for 3 minutes. Next, a high-pressure mercury lamp was used to obtain an integrated light amount of 600 mJ / cm. 2 The laminate was irradiated with ultraviolet light so that the thickness of the protective layer was 3 μm. The resin substrate was then peeled off from the laminate to obtain a polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure.
[0192] [Example 2-2] 15 parts of an epoxy resin having a biphenyl skeleton (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX4000) and 10 parts by weight of an oxetane resin (manufactured by Toagosei Co., Ltd., product name: Aron Oxetane (registered trademark) OXT-221) were dissolved in 73 parts of methyl ethyl ketone to obtain an epoxy resin solution. 2 parts of a photocationic polymerization initiator (manufactured by San-Apro Co., Ltd., product name: CPI (registered trademark)-100P) were added to the obtained epoxy resin solution to obtain a protective layer-forming composition. A polarizing plate having a protective layer (photocationic cured layer of epoxy resin) / polarizer configuration was obtained in the same manner as in Example 2-1, except that the protective layer-forming composition was obtained using this epoxy resin solution, dye baths with various iodine concentrations (weight ratio of iodine to potassium iodide = 1:7) were used, and the stretching ratio of the underwater stretching when preparing the polarizer was 1.25 times (total stretching ratio: 3.0 times).
[0193] [Example 2-3] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-2, except that dye baths with various iodine concentrations (weight ratio of iodine to potassium iodide = 1:7) were used and the stretching ratio in the underwater stretching when preparing the polarizer was 1.46 times (total stretching ratio: 3.5 times).
[0194] [Example 2-4] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-2, except that dye baths with various iodine concentrations (weight ratio of iodine to potassium iodide = 1:7) were used and the stretching ratio in the underwater stretching when preparing the polarizer was 1.67 times (total stretching ratio: 4.0 times).
[0195] [Example 2-5] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-2, except that dye baths with various iodine concentrations (weight ratio of iodine to potassium iodide = 1:7) were used and the stretching ratio in the underwater stretching when preparing the polarizer was 1.88 times (total stretching ratio: 4.5 times).
[0196] [Example 2-6] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-1, except that a bisphenol-type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) 828) was used instead of the epoxy resin having a biphenyl skeleton.
[0197] [Example 2-7] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-3, except that a bisphenol-type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) 828) was used instead of the epoxy resin having a biphenyl skeleton.
[0198] [Example 2-8] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-1, except that a hydrogenated bisphenol type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX8000) was used instead of the epoxy resin having a biphenyl skeleton.
[0199] [Example 2-9] A polarizing plate having a protective layer (photocationically cured layer of epoxy resin) / polarizer structure was obtained in the same manner as in Example 2-3, except that a hydrogenated bisphenol type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX8000) was used instead of the epoxy resin having a biphenyl skeleton.
[0200] [Example 2-10] 1. Preparation of Polarizing Plates A polarizing plate having a structure of protective layer (photocationically cured layer of epoxy resin) / polarizer was obtained in the same manner as in Example 2-3.
[0201] 2. Preparation of the first retardation layer Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.
[0202] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 130μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched while adjusting so as to obtain a predetermined retardation, and a retardation film having a thickness of 48μm was obtained. The stretching conditions were a stretching temperature of 143°C and a stretching ratio of 2.8 times in the width direction. The Re(550) of the obtained retardation film was 141nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.
[0203] 3. Second retardation layer A retardation film (manufactured by Dai Nippon Printing Co., Ltd., "MCP-N") whose refractive index characteristics satisfy the relationship nz>nx=ny and whose thickness direction retardation Rth(550) is -135 nm was used as the second retardation layer.
[0204] 4. Preparation of polarizing plate with retardation layer First, the second retardation layer was attached to the first retardation layer surface via an ultraviolet curing adhesive. Then, the first retardation layer surface of the laminate of the first retardation layer / second retardation layer was attached to the polarizer surface of the polarizing plate via an acrylic adhesive layer having a thickness of 12 μm. At that time, the first retardation layer was attached so that the slow axis of the first retardation layer and the absorption axis of the polarizer were at an angle of 45°. In this way, a retardation layer-attached polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer / first retardation layer / second retardation layer was obtained.
[0205] [Example 3-1] 1. Preparation of a laminate of polarizer / resin substrate In the same manner as in Example 1-1, a polarizer having a thickness of 6.7 μm was formed on a resin substrate to prepare a laminate of the polarizer and the resin substrate. 2. Preparation of the Protective Layer 20 parts of epoxy resin 1 (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) 1256B40, weight average molecular weight: 40000, epoxy equivalent: 7350) was dissolved in 80 parts of methyl ethyl ketone to obtain an epoxy resin solution (20%). This epoxy resin solution was applied to the polarizer surface of the laminate using a wire bar, and the coating film was dried at 60°C for 3 minutes to form a protective layer constituted as a solidified coating film. The thickness of the protective layer was 3 μm. Next, the resin substrate was peeled off from the obtained laminate to obtain a polarizing plate having a configuration of protective layer (solidified layer of coating film of epoxy resin) / polarizer.
[0206] [Example 3-2] A polarizing plate having a protective layer (solidified layer of epoxy resin coating film) / polarizer structure was obtained in the same manner as in Example 3-1, except that epoxy resin 2 (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX6954BH30, weight average molecular weight: 36000, epoxy equivalent: 13000) was used instead of epoxy resin 1.
[0207] [Example 4] A polarizing plate having a protective layer (solidified coating film) / polarizer structure was obtained in the same manner as in Example 1-1, except that no easy-adhesion layer was formed (i.e., the protective layer was formed directly on the polarizer) and that a water-based polyester resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "Polyester WR905") was used.
[0208] [Example 5] A polarizing plate having a protective layer (solidified coating film) / polarizer configuration was obtained in the same manner as in Example 1-1, except that no easy-adhesion layer was formed (i.e., the protective layer was formed directly on the polarizer) and that a water-based polyurethane resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Superflex SF210") was used.
[0209] [Comparative Example 1] A polarizing plate having a structure of protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-1, except that the underwater stretching ratio in producing the polarizer was 2.29 times (total stretching ratio: 5.5 times).
[0210] [Comparative Example 2] A polarizing plate having a structure of hard coat layer / protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-2, except that the underwater stretching ratio in producing the polarizer was 2.29 times (total stretching ratio: 5.5 times).
[0211] [Comparative Example 3] A polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 2-3, except that dye baths with various iodine concentrations (weight ratio of iodine to potassium iodide = 1:7) were used and the stretching ratio in the underwater stretching when preparing the polarizer was set to 2.29 times (total stretching ratio: 5.5 times).
[0212] [Comparative Example 4] A polarizing plate with a retardation layer having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer / first retardation layer / second retardation layer was obtained in the same manner as in Example 2-10, except that the stretching ratio in the underwater stretching when preparing the polarizer was 2.29 times (total stretching ratio: 5.5 times).
[0213] [Comparative Example 5] A polarizing plate having a structure of protective layer (solidified coating film) / easy-adhesion layer / polarizer was obtained in the same manner as in Example 1-7, except that the underwater stretching ratio in producing the polarizer was 2.29 times (total stretching ratio: 5.5 times).
[0214] [Comparative Example 6] A polarizing plate having a protective layer (acrylic resin film) / polarizer structure was obtained in the same manner as in Example 1-1, except that the stretching ratio of the underwater stretching when preparing the polarizer was 2.29 times (total stretching ratio: 5.5 times) and an acrylic resin film (refractive index: 1.50, thickness: 20 μm) with easy-adhesion treatment on one side was used as the protective layer. The acrylic resin film was directly bonded to the polarizer surface via an ultraviolet curing adhesive. Specifically, the curing adhesive was applied so that the total thickness of the curing adhesive was 1.0 μm, and the two were bonded using a rolling machine. Thereafter, UV rays were irradiated from the acrylic resin film side to cure the adhesive.
[0215] The evaluation results are shown in Tables 1 to 3. [Table 1]
[0216] [Table 2]
[0217] [Table 3]
[0218] As shown in Tables 1 to 3, the polarizing plates of the examples using the polarizer in which the orientation degree of the PVA resin is controlled to a predetermined state (as a result, the polarizer has a piercing strength in a predetermined range) suppress cracking during heating even when the protective layer is extremely thin. In addition, the polarizing plates having a specific protective layer show excellent humidity durability.
[0219] 5 to 7 show the relationship between the single transmittance of the polarizers (polarizers with total stretch ratios of 3.0, 3.5, 4.0, 4.5, or 5.5 times) used in the examples and comparative examples and the Δn, in-plane retardation, or orientation function of the PVA. As shown in Figs. 5 to 7 and Tables 1 to 3, the polarizers satisfying formula (1), formula (2), and / or formula (3) exhibit a piercing strength equal to or less than a predetermined value, and it is also found that the polarizing plate produced using such a polarizer is prevented from cracking when heated, even when the protective layer has an extremely thin thickness. [Industrial Applicability]
[0220] The polarizing plate of the present invention is preferably used in image display devices. Examples of image display devices include portable devices such as personal digital assistants (PDAs), smartphones, mobile phones, watches, digital cameras, and portable game machines; office automation devices such as personal computer monitors, notebook computers, and copy machines; home electric appliances such as video cameras, televisions, and microwave ovens; in-vehicle devices such as back monitors, monitors for car navigation systems, and car audio; exhibition devices such as digital signage and information monitors for commercial stores; security devices such as surveillance monitors; and nursing and medical devices such as nursing monitors and medical monitors. [Explanation of symbols]
[0221] 10 Polarizer 20 First protective layer 100 Polarizing Plate 110 Retardation layer 200 Polarizing plate with retardation layer
Claims
[Claim 1] A polarizing plate having a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer disposed on one side of the polarizer, When the single transmittance of the polarizer is x % and the birefringence of the polyvinyl alcohol-based resin is y, the polarizer satisfies the following formula (1): y<-0.011x+0.525 (1) The protective layer is made of a resin film having a thickness of 10 μm or less.
Citation Information
Patent Citations
Polarizer protection film and polarizing plate
JP2015210474A